The interaction and photostability of some xanthenes and selected azo sensitizing dyes with TiO2 nanoparticles - D. EL Mekkawi; M. S. A. Abdel-Mottaleb (International Journal of Photoenergy)
We have tested simple Graetzel-type solar cells using semiconductor thin films consisting of TiO2 nanoparticles and some electron injecting dyes. The possibility of using xanthenes (rhodamine 101, fluorescein and 5(6)-carboxyfluorescein) and selected azo dyes (alizarin yellow R, alizarin yellow 2G and carboxyaesenazo) as sensitizers has been explored. Fluorescence and electronic absorption measurements revealed complex formation between the chosen dyes and the surface of the colloidal TiO2. The apparent association constants (Kapp) of the surface complexes have been estimated and are correlated with the dyeinduced negative shifts of the reduction potential of colloidal TiO2 nanoparticles. Moreover, due to its utmost importance, photostability of the organic dyes in absence and presence of colloidal TiO2 nanoparticles and the influence of the used electrolyte have been examined. The results point to a remarkable enhancement of photostability in the presence of the electrolyte (I3−/I−), which is attributed to fast regeneration of the neutral dye via the redox couple of the electrolyte. Furthermore, photocurrent action spectrum of the fabricated and tested DSC shows the origin of photoelectric output to be optical absorption of the dye used.